The Policy-Making Model Based on Conflict of Interest Management in Crisis Conditions in the Country\'s Health System (Case of Study: The Experience of COVID-19) - Mahnaz sabzi; abbas Monavarian; Tayebeh Abbasi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat)
Background: Policy-making is one of the management functions in the health system, and according to the main goal of the health system, which is health promotion, health system approaches are advancing in the light of presenting a policy-making model based on conflict of interest management. Therefore, the purpose of this research is to present a policy-making model based on conflict of interest management in crisis conditions in the country's health system during the period of the COVID-19 crisis. Methods: This research is an applied research in terms of purpose, and has a qualitative approach, and the multi-grounded theory method was used as the research method. This study was conducted by collecting data, through library studies and semi-structured interviews with 12 experts of the country's health system through theoretical sampling until the saturation point was reached. The inclusion criteria were familiarity with the policy-making process in the health system and having at least a master's degree related to policy-making, and the exclusion criterion was lack of desire and motivation. Data analysis was done in three stages of open coding, axial coding, and selective coding using MaxQDA10 software. In order to obtain the reliability and validity of the data, 2 methods of reviewing the participants and Lincoln and Guba (1985) approach were used. Results: The findings showed that the policy-making model based on conflict of interest management includes 74 sub-categories in the form of 18 main categories of causal, contextual, intervening conditions, central phenomenon, consequences, and strategies. It indicates that selecting policy-maker, the personality characteristics of the policy-maker, the principles of health system policy-making, and medical resources and equipment are causal factors affecting policy-making based on conflict of interest management, which predicts consequences at the micro and macro levels. Conclusion: The policy-making model based on conflict of interest management comprehensively identifies factors such as the personality characteristics of policymakers and health system resources as influential factors. This model shows that considering these factors, consequences can be predicted at the micro and macro levels. Therefore, effective conflict of interest management requires attention to various conditions and factors, so that decisions can be made optimally and without conflict.